(untitled) (Semiárida, 2020)
To evaluate the effect of localized application of herbicides by contact, in Desmodium incanum, this trial was conducted during a period of 353 days. The experimental design was a split plot arranged in a randomized block design with three replications in a factorial arrangement [(5x3) +1], five herbicides plus the control and three evaluation periods. The plots corresponded to herbicides, doses were locate: 1.5, 3.0 and 4.5 L ha -1 of Tordon, Aminol 806, Garlon, Grazon e Plenum, being composed by 8 tables arranged on a fixed line. Prior to application, was made a survey, another in 60 and 353 days after application. For the herbicides application, was used a chemical applicator, which consists in an adjustable height platform, and it is contact is only with the target plant. The use of chemical applicator was effective for controlling undesirable species besides not interfere on Desmodium incanum frequency besides being interesting for selective cleaning and preservation of the native vegetation.